THE ROLE OF ISLAMIC FINANCIAL COOPERATIVE (BMT) IN POVERTY ALLEVIATION THROUGH EMPOWERING MICRO, SMALL, AND MEDIUM ENTERPRENEURS - Kamaliyah, Fitrah (Universitas Airlangga, 2018)
The purpose of this study to analyze the role of BMT on MSMEs quality of life by taking a casestudy of BMT Bina Umat Sejahtera in Yogyakarta city. A survey on 53 respondents was conducted on September-November 2015. Non-parametric tests were applied in this study to analyze correlation between variables and CIBEST, MSMPI and IPI MODEL were employed as poverty measurement tools. This study found that financing throughthe entrepreneurs was effectiveto increase their income. Age, duration of installment, financing amount, household income and expenditure before financing found as significant factorsaffecting to household income after financing. Overall, BMT's Performance was proven to be able change the quality of life of respondentsin three models of poverty measurement positively.The results of this study are expected to BMT strategies so that financing customers can improve their standard of living as well as increase their level of spirituality